Effect of laser‐activated irrigation on biofilms in artificial root canals. (16th April 2016) - De Meyer, S.; Meire, M. A.; Coenye, T.; De Moor, R. J. G.
Abstract: Aim: To evaluate the antimicrobial effect of laser‐activated irrigation (LAI) on biofilms formed in simulated root canals. Methodology: A dual‐species biofilm of Enterococcus faecalis and Streptococcus mutans was grown in a resin root canal model. Biofilms were formed over 48 h and subsequently subjected to the following treatments, all executed for 20 s: syringe irrigation (SI) with a 27G needle, ultrasonically activated irrigation (UAI) with a size 20 Irrisafe file, and LAI with a 2940 nm Er:YAG laser (20 Hz, 50 μs, 20 or 40 mJ, conical fibre tip at two positions). Tests were performed with both sterile saline as well as NaOCl (2.5%) as the irrigant. Surviving bacteria were harvested and the number of CFU was determined by plate counting and compared across groups (anova, P ≤ 0.05). Results: Using saline as the irrigant, significant reductions in viable counts compared to untreated controls were observed for ultrasonically activated irrigation (0.52 log10 reduction) and for all laser‐activated irrigation groups (>1 log10 reduction), but not for syringe irrigation (<0.25 log10 reduction). The reductions in the laser‐activated irrigation groups were significantly greater than those of ultrasonically activated irrigation. With NaOCl as the irrigant, significant reductions (>2.2 log10 units) in the number of attached bacteria were observed for all treatment groups with no significant differences between laser‐activated and ultrasonically activated irrigation. Conclusions: Within the limitations of this in vitro set‐up, laser‐activated irrigation removed more biofilm than ultrasonically activated irrigation when using saline as the irrigant, indicating greater physical biofilm removal. The use of NaOCl resulted in greater biofilm reduction with no significant differences between treatment groups.